Determination of optimal concentration of deglycyrrhizinated licorice root extract for preventing dental caries using a bacterial model system - Sug-Joon Ahn; Young-Doo Song; Su-Jung Mah; Eun-Jung Cho; Joong-Ki Kook (Elsevier, 2014)
Background/purpose: In prior studies, we induced the antimicrobial activity of deglycyrrhizinated licorice root extract (DG-LRE) by inhibiting the growth and biofilm formation of Streptococcus mutans UA159. Here, we used clinical strains of mutans streptococci (MS) collected from Koreans to determine the optimal concentration of DG-LRE for oral hygiene products to prevent dental caries. Materials and methods: Antimicrobial effects of DG-LRE against 14 clinical strains of MS were evaluated through the minimum inhibitory concentration, minimum bactericidal concentration, time-kill assay, and biofilm-forming assay. Results: Minimum inhibitory concentration and minimum bactericidal concentration values of DG-LRE against the clinical strains of MS ranged from 4 μg/mL to 8 μg/mL and from 8 μg/mL to 16 μg/mL, respectively. Time-kill assay demonstrated that the antimicrobial effects of DG-LRE primarily resulted from bactericidal activity. DG-LRE significantly decreased the biofilm formation of S. mutans ranging from 57.6% to 92.8% at 16 μg/mL. Conclusion: These findings reveal that a DG-LRE concentration of 16 μg/mL may be used to prevent dental caries in Koreans.